Perceptions and Beliefs Regarding NSAIDs in the Asia-Pacific Region - Ho KY (Journal of Pain Research, 2020)
Kok-Yuen Ho The Pain Clinic, Mount Alvernia Hospital, SingaporeCorrespondence: Kok-Yuen HoThe Pain Clinic, Mount Alvernia Hospital, 820 Thomson Road – 07-59, 574623, SingaporeTel/Fax +65 6 254 5447Email drho@thepainclinic.com.sgBackground: Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used in the treatment of pain and inflammation. However, chronic NSAID use may result in gastrointestinal (GI), cardiovascular (CV), renal or other safety concerns, especially in high-risk populations. The aim of this review is to systematically identify relevant literature and to organize available evidence for perceptions or beliefs of physicians and patients about the safety and efficacy of NSAIDs.Methods: A systematic literature search was conducted in MEDLINE® (through PubMed®), Embase® (through Ovid®), and the Cochrane Library. Additional unstructured searches were conducted using Google Scholar™ and Google. The scope of this study did not include grey literature searches or handpicking of cross references. This systematic analysis was conducted with a special interest in studies conducted in the Asia-Pacific (APAC) region and information related to the COX-2 (cyclooxygenase-2) selective inhibitors.Results: Out of a total of 2822 studies retrieved from different databases (PubMed®, Cochrane, Google Scholar™ and Embase®), 99 (3.5%) met the inclusion criteria. Further, out of these 99 studies, 23 APAC region studies were analyzed. The common perceptions were related to GI, CV, renal and respiratory safety, efficacy and COX-2 inhibitors.Conclusion: Overall, the level of awareness among patients regarding NSAIDs was observed to be considerably poor. Moreover, risk stratification by physicians must be practiced in order to decrease the incidence of adverse events.Keywords: cardiovascular, COX-2 inhibitors, efficacy, gastrointestinal, renal, respiratory